'Invincible summer' : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Creative Writing at Massey University, New Zealand - Cush-Hunter, Jeanita (Massey University, 2019)
Why is silence considered to be golden? This Master of Creative writing thesis questions why so many women suffer in silence and dares to break that silence. The thesis examines the genre of the personal essay in a contemporary context and explores its relevance and utility for the expression of the stories of women’s suffering. The thesis consists of two sections, creative and critical, and has an eighty percent creative component and a twenty percent critical component. Invincible Summer is divided into two parts. The first part is titled ‘Concerto’ and consists of 8 personal essays. This section explores content and subject matter that is specifically about and, relevant to, my personal experiences with suffering as a woman including Anorexia nervosa, Obsessive-Compulsive Disorder, Postpartum trauma and being the mother of a child with Autism. The second part is titled ‘Risoluto’ and it is structured around critical analysis of the communication of suffering experienced by other women writers including Ashleigh Young, Maggie O’Farrell, and Leslie Jamison. As a whole, but most directly in this essay, the thesis questions and investigates the criticisms leveled against the personal essay, particularly the accusations of solipsism, narrow scope, and sensationalism. The thesis employs a variety of approaches toward the personal essay in order to explore the diversity and flexibility of the genre as a form of autobiographical writing. These personal essays utilise different approaches to structure and are built around scenes from specific times in my life. The essays explore the use of patterns and connections through personal writing in a way that allows each essay to be effective as a stand-alone essay while also functioning as part of a whole through the interweaving of common themes and events. By taking this approach, I aimed to portray the essays as snapshots of unique moments in order to demonstrate how fragments of a life may be perceived as isolated incidents while still forming part of a whole cohesive picture. My purpose when creating this thesis was to demonstrate the versatility, power and accessibility of the personal essay for women who write about their suffering. In the creative component, I aimed to demonstrate the flexibility of the personal essay as a framework that is capable of supporting multiple stories from multiple stages in a writer’s life. In the critical component, I defend the personal essay’s place in a contemporary context and argue against specific criticisms in order to justify that self-disclosure is an acceptable and respectable form of communication.
Keywords: New Zealand literature; 21st century; Essay; Women in literature; Suffering in literature; 360201 Creative writing (incl. scriptwriting); 360201 Creative writing (incl. scriptwriting)